Mewujudkan Profesionalisme Guru dalam Mengajar melalui Program Supervisi Akademik Kepala Sekolah - Diah Rina Miftakhi; Yopi Malagola (Journal Of Administration and Educational Management (ALIGNMENT), 2025)
This study aims to describe and analyze the role of principals' academic supervision in realizing teacher professionalism in teaching in senior high schools. The research method used was a qualitative approach with a purposive sampling technique. Data sources included principals, school supervisors, school committees, and teachers at several public and private high schools in Sleman Regency. Data collection was conducted through interviews, observation, and documentation. Data analysis used the Miles and Huberman model, which includes data reduction, data presentation, and verification. Data validity was maintained through triangulation techniques. The results indicate that academic supervision has been implemented by principals through the stages of planning, implementation, evaluation, follow-up, and reporting, and has made a positive contribution to improving teacher professionalism, particularly in lesson planning, lesson implementation, and classroom management. However, the implementation of academic supervision still faces several obstacles, including limited time for principals, limited supervisory teams, and suboptimal follow-up of supervision results. In conclusion, the principal's academic supervision plays a crucial role in fostering teacher professionalism in teaching. However, strengthened planning, ongoing evaluation, consistent follow-up, and enhanced competency of the principal and supervisory team are needed to ensure optimal academic supervision impacts the quality of learning.   Keywords: Academic Supervision, Principal, Teacher Professionalism, Learning